Developments in the application of Intensive Comprehensive Aphasia Programs: an international survey of practice. Issue 20 (25th September 2022) - Rose, Miranda L.; Pierce, John E.; Scharp, Victoria L.; Off, Catherine A.; Babbitt, Edna M.; Griffin-Musick, Jenna R.; Cherney, Leora R.
Abstract: Purpose: Intensive Comprehensive Aphasia Programs (ICAPs) were first described in 2013 with an international survey documenting 12 unique programs. ICAPs involve high dose intervention delivered in both group and individual settings, targeting communication across impairment, functioning, participation, and contextual domains. In this study, we aimed to investigate international growth in ICAPs. Materials and methods: We developed a 43-item questionnaire expanding on the original 2013 version to investigate program modifications, activities, protocolised therapies, software and apps, and family involvement. The survey was disseminated to aphasia clinicians and researchers internationally (November 2019–February 2020). Results: Thirty-nine unique respondents completed the survey from nine countries. Twenty-one met the criteria for an ICAP or modified ICAP (mICAP): 14 ICAPs; 7 mICAPs, and 13 of these were new programs. ICAPs differed from mICAPs with greater emphasis on group sessions, use of technology, total communication, advocacy, and art activities. A large range of protocolised therapies were used across programs. An increased focus on mood and psychosocial well-being was observed compared to the 2013 survey. Conclusions: The number and comprehensiveness of ICAPs has grown since 2013 with development of modified versions. Future research should focus on comparative efficacy of ICAPs/mICAPs and other forms of aphasia interventions and factors underpinning growth and sustainability. Implications for Rehabilitation: Clinicians who coordinate or are considering commencing an ICAP in future can use these results to consider the design of their program. Coordinators should carefully consider the components of their ICAPs and advise consumers whether they meet the definition of an ICAP or a mICAP. With the increasing number of ICAPs across the globe, clinicians commencing an ICAP may wish to contact existing ICAPs within their country for advice. Program sustainability may be challenging and these results provide an indication of some of the key challenges coordinators may face.